Patterns and controls on island‐wide aboveground biomass accumulation in second‐growth forests of Puerto Rico. (28th July 2022) - Martinuzzi, Sebastián; Cook, Bruce D.; Helmer, Eileen H.; Keller, Michael; Locke, Dexter H.; Marcano‐Vega, Humfredo; Uriarte, María; Morton, Douglas C.
Abstract: Understanding the heterogeneity of biomass accumulation in second‐growth tropical forests following land use abandonment is important for informing ecosystem carbon models and forest restoration efforts. There is an urgent need for a broad sample of second‐growth forests to enhance our knowledge of carbon accumulation in human‐dominated landscapes, especially for older forests. Puerto Rico has predominantly second‐growth forests, ranging in age from approximately 25 to more than 80 years. We used an island‐wide sample of airborne lidar from the NASA Goddard Lidar, Hyperspectral, and Thermal (G‐LiHT) Airborne Imager collected on March 2017, forest inventory data, and data on forest age, precipitation, soils, and land use to estimate aboveground biomass stocks in moist and wet, second‐growth tropical forests. Biomass accumulation rates in Puerto Rico were lower, on average, than in other Neotropical forests. Median biomass across >16, 700 ha of older second‐growth forests was 105 Mg ha −1, and sampled biomass rarely surpassed 250 Mg ha −1 . Differences in biomass by age were large and persistent across different substrates and land uses, with a plateau in the pattern of island‐wide biomass accumulation after about 33 years. A spatial regression model showed that multiple factors were related to biomass accumulation, including time since abandonment, geologic substrate, past land use as coffee or pasture, precipitation, topographic wetness index, and slope. Our findings have important consequences for the total carbon storage and expected climate mitigation benefits of large‐scale reforestation efforts, and highlight the value of airborne lidar for quantifying biomass variability in complex tropical landscapes. Abstract in Spanish is available with online material. Abstract : Understanding the heterogeneity of biomass accumulation in second‐growth tropical forests following land use abandonment is important for informing ecosystem carbon models and forest restoration efforts. Using airborne lidar data, we quantify patterns and controls on aboveground biomass accumulation in second‐growth forests of Puerto Rico. Resumen: Entender la variabilidad de la acumulación de biomasa en los bosques tropicales secundarios originados luego del abandono del uso de la tierra es importante para informar modelos de ecosistemas, asi como esfuerzos de restauración. Existe una necesidad urgente de ampliar la muestra de bosques secundarios, especialmente de aquellos más maduros, para aumentar nuestro conocimiento de la acumulación de carbono en paisajes dominados por humanos. Puerto Rico posee una abundancia de bosques secundarios cuya edad oscila entre aproximadamente 25 y más de 80 años. Utilizamos datos de lidar aéreo colectados a través de la isla con el sensor Goddard Lidar, Hyperspectral, and Thermal (G‐LiHT) de NASA en Marzo de 2017, parcelas forestales, y datos sobre la edad del bosque, precipitación, suelos, y uso de la tierra, para estimar la biomasa aérea en los bosques tropicales secundarios húmedos y muy húmedos. La tasa de acumulación de biomasa en Puerto Rico fué más baja, en promedio, que en otros bosques neotropicales. La mediana de la biomasa en >16 700 ha de bosques secundario fue 105 Mg ha −1, y la biomasa rara vez superó los 250 Mg ha −1 . Las diferencias en la biomasa por edad fueron grandes y persistentes en diferentes sustratos y usos de la tierra, con una meseta en el patrón de acumulación de biomasa a nivel isla después de 33 años. El modelo de regresión espacial mostró que múltiples factores se relacionaron con la acumulación de biomasa, incluidos el tiempo desde el abandono del suelo, el sustrato geológico, el uso anterior del suelo como café o pastura, la precipitación, índice topográfico de humedad, y pendiente. Nuestros resultados tienes consecuencias importantes para el almacenamiento total de carbono y los beneficios esperados de mitigación climática provenientes de esfuerzos de reforestación a gran escala, y resaltan el valor del lidar aéreo para cuantificar la variabilidad de la biomasa en paisajes tropicales complejos.